Analisis Kelayakan Potensi Destinasi Wisata di Kampung Saradan/Sawah Abadi Kelurahan Cisurupan, Kecamatan Pasirluyu Kota Bandung - Afriza, Lia; Agustiani, Indah Nur (Manajemen dan Pariwisata, 2024)
The city of Bandung as a leading tourist destination was also strengthened based on the results of a survey conducted by the Fastbooking.com site at the end of 2014. At the world level, the city of Bandung is in the 21st position in the most popular/favorite tourist destination in the world. The advantages of the city of Bandung also come from the level of comfort and livability of the city. The city of Bandung still has the potential to become an attraction and tourist destination, namely eternal rice fields which function as food fields as well as Green Open Space (RTH) with an area of ??32.8 hectares. The eternal rice field area is located in the Cisurupan Village area, Pasirluyu District, which is also included in the North Bandung Area (KBU). This research is directed at analyzing the feasibility of tourism potential and data analysis in the Sawah Abadi area, Cisurupan Village, Pasirluyu District, Bandung City within the scope of market aspects, technical/operational and management aspects, as well as financial aspects. The aim of this research is to determine the tourism potential so that it can become a tourist area. The research method used is descriptive, which describes a phenomenon as it is by examining it regularly, prioritizing objectivity, and carrying it out carefully. There is no treatment given or controlled, and there is no hypothesis testing. The targeted output is to produce a written report and it is hoped that this output can be used by the community in the Sawah Abadi Area, Cisurupan Village, Pasirluyu District, Bandung City.